Evaluation of the potential of chitosan/β-1,3-glucan/hydroxyapatite material as a scaffold for living bone graft production in vitro by comparison of ADSC and BMDSC behaviour on its surface - Przekora, Agata; Vandrovcová, Marta; Trávníčková, Martina; Pajorova, Julia; Molitor, Martin; Ginalska, Grazyna; Bačáková, Lucie (Biomedical materials, 2017)
The opinion regarding the origin of adult stem cells that should be used for living bone construct generation is strongly divided in the scientific community. In this study, the potential of chitosan/β-1,3-glucan/hydroxyapatite (chit/glu/HA) material as a scaffold for bone regeneration applications was evaluated by behaviour comparison of adult stem cells derived from both origins-adipose derived mesenchymal stem cell (ADSC) tissue and bone marrow derived mesenchymal stem cells (BMDSCs). In the case of ADSC isolation, low and high negative pressures were applied during a liposuction procedure in order to determine if negative pressure settings may have an impact on subsequent cell behaviour in vitro. The obtained results demonstrated that the chit/glu/HA material is a promising candidate to be used for living bone graft production in vitro as both ADSCs and BMDSCs revealed a satisfactory proliferation and differentiation ability on its surface. Nevertheless, BMDSCs would be a better choice of adult stem cells since they were better spread, more strongly attached and showed a more superior proliferation and differentiation ability than ADSCs when cultured on the chit/glu/HA scaffold. However, if BMDSCs cannot be isolated, ADSCs may be used for bone construct production but lipoaspirate should be collected under low negative pressure (-200 mm Hg), as high negative pressure (-700 mmHg) applied during liposuction surgery may retard subsequent ADSC proliferation and type I collagen production.
Keywords: testování materiálů; mezenchymální kmenové buňky; Focal Adhesions; biokompatibilní materiály; Cell Movement; Cells, Cultured; beta-glukany; Bone Regeneration; Cell Proliferation; Cell Differentiation; Humans; pohyb buněk; fokální adheze; Chitosan; tuková tkáň; Adipose Tissue; beta-Glucans; proliferace buněk; Tissue Scaffolds; Biocompatible Materials; chitosan; kultivované buňky; tkáňové podpůrné struktury; regenerace kostí; Mesenchymal Stem Cells; hydroxyapatit; Osteogenesis; lidé; osteogeneze; Materials Testing; Durapatite; buněčná diferenciace